Star wars : war of the bounty hunters - Soule, Charles (Marvel Worldwide, a subsidirary of Marvel Enterprises, Inc., 2021)
"The hunt for Han! Chewbacca has heard from an old friend with intelligence on the location of notorious bounty hunter Boba Fett, who is in possession of the carbon-frozen body of Han Solo. Along with Luke Skywalker, the loyal Wookiee sets off in search of his lost friend, on an adventure to Nar Shadaa…better known as the Smuggler's Moon! But this mission may prevent plucky astromech droid R2-D2 from passing along a crucial message to Luke--a message that will affect the fate of the entire Jedi Order! The saga of Star Wars continues to surprise!"--